2020
DOI: 10.3390/app10020511
|View full text |Cite
|
Sign up to set email alerts
|

Jet Noise in Airframe Integration and Shielding

Abstract: This paper reviews and presents new results on the effect of airframe integration and shielding on jet noise. Available experimental data on integration effects are analyzed. The available options for the computation of jet noise are discussed, and a practical numerical approach for the present topic is recommended. Here, it is demonstrated how a hybrid large eddy simulation—unsteady Reynolds-averaged Navier-Stokes approach can be implemented to simulate the effect of shielding on radiated jet noise. This appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 81 publications
0
3
0
Order By: Relevance
“…Sensitivity studies of the extent of the FWH up to x/D=40 is investigated previously and reported by Salehian and Mankbadi. 1 Such grid spacing on FWH surface would ensure capturing acoustic waves up to Strouhal number St=fD/Uj=0.350.4 where f is the frequency. This maximum frequency represents up to 75% of the spectra (in logarithmic scale) shown in experimental results and contains most of the trend in spectral analysis of the acoustic signal, such as the peak frequency of St=0.1 observed in experimental results.…”
Section: Numerical Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…Sensitivity studies of the extent of the FWH up to x/D=40 is investigated previously and reported by Salehian and Mankbadi. 1 Such grid spacing on FWH surface would ensure capturing acoustic waves up to Strouhal number St=fD/Uj=0.350.4 where f is the frequency. This maximum frequency represents up to 75% of the spectra (in logarithmic scale) shown in experimental results and contains most of the trend in spectral analysis of the acoustic signal, such as the peak frequency of St=0.1 observed in experimental results.…”
Section: Numerical Approachmentioning
confidence: 99%
“…This is generally referred to as the installation noise or interaction effect. A detailed review on jet-surface interaction and shielding effect on jet noise is provided by Salehian and Mankbadi 1 The focus here is on the case where there is some distance between the jet plume and the airframe surface/wing. In several pursued aircraft design configuration concepts, the engine is mounted on top.…”
Section: Introductionmentioning
confidence: 99%
“…In the same way, the wall pressure load generated by the external turbulent boundary layer and by the impact of the jet plume over the rear part of the fuselage or on the wing pressure side can cause fatigue problems because of the induced vibrations. Above all, in future configurations, like the blended wing body where the fuselage efficiently shields the jet noise, the jet-induced wall pressure load could significantly stress the aircraft panels (Liebeck 2002; Salehian & Mankbadi 2020).…”
Section: Introductionmentioning
confidence: 99%